Studi Eksperimental Burner untuk Bahan Bakar Pirolisis Polypropylene: Analisis Emisi Gas Buang - Aditya Wahyu Pratama; Novangga Adi Mulyono; Audha Fitrah Aulina; Reynaldi Akbar Ali; Faruq Avero Azhar; Andik Irawan; Wijaya, Hardian Asep (Jurnal Teknik Terapan, 2025)
Alternative fuels derived from the pyrolysis of Polypropylene (PP) plastic waste present a promising approach to decreasing reliance on fossil fuels while also addressing plastic waste reduction. his experimental study investigates the exhaust emission characteristics of a modified burner equipped with a blower compared to a conventional burner. The experimental setup utilized specially designed burners to enhance the combustion performance of PP pyrolysis oil. Fuel blends containing 5%, 10%, and 20% PP pyrolysis oil mixed with Pertamax were tested. Emission parameters, including CO, CO₂, HC, and NOx concentrations, were measured under idle operating conditions using a gas analyzer. The findings revealed that the modified burner operating with a 10% PP pyrolysis oil blend produced lower HC, O₂, and lambda emission levels than the standard burner. Conversely, CO and CO₂ emissions were found to be higher for the modified burner configuration. In both burner types, NOx emissions were not detected.